Repair Strategies of Teacher’s Talk in EFL Classroom - Sukma Nur Ardini (ETERNAL (English Teaching Journal), 2015)
This study investigated the curiosity of how an eminent senior high teacher handled the communication in EFL classroom when he has problems in expressing ideas during the learning process where English is unlikely to be spoken than Javanese. It examined two repair strategies; repetition and self-initiated repair since these two are prominent features of daily communication mostly in the setting of English as a foreign language. It was a classroom discourse analysis study which used a descriptive qualitative approach. Numbers used in the form of percentage to support the findings. The participant of this study was an eminent teacher of a private senior high in Semarang. The learning session was video recorded then was carefully transcribed. Then, the repair strategies of the teacher’s talk were analyzed through the study. The findings revealed that self-initiated repair was used less frequently than repetition. There were 45 out of 210 utterances done for repetition (13.81%) and 16 out of 210 utterances done for self-initiated (7.61%). It was also found the combination of those two repair strategies in one utterance. The findings indicate that the effort of the teacher to build English speaking classroom atmosphere is very high even though the students were lack of motivation in speaking English. Yet, the teacher shows the repair strategy mostly in the beginning of the learning session, but he finally made it through the rest of the session. The findings may inspire those of many other English teachers, especially in Indonesia, in giving positive contribution in building EFL classroom.